The Effect of Transparency and Accountability on Financial Management in Dauh Puri Klod Village, West Denpasar District - Kadek Dwi Septiantara; Ni Made Vita Indriyani; Kadek Goldina Puteri Dewi (Journal of Governance, Taxation and Auditing, 2026)
Indonesia's regional autonomy policy has brought fundamental changes in governance, particularly in the area of ​​village-level public financial management. However, there is a gap between the normative objectives of the policy and the actual practice of village financial management in the field, particularly in terms of implementing village fund policies. Understanding the impact of accountability and transparency on financial management is the main driver of this research. This research was conducted in Dauh Puri Klod Village, West Denpasar Regency. The study involved 100 residents of Dauh Puri Klod Village. Multiple linear regression was used. The results showed that accountability and transparency improve financial resource management. The researcher can recommend: Dauh Puri Klod Village, West Denpasar Regency is expected to make announcements, establish clear SOPs for report preparation, optimally utilize village financial applications, conduct regular monitoring and impose sanctions for late submissions, conduct periodic and gradual evaluations of village financial management to ensure proper implementation, consistently prepare budgets, and use village funds according to plan.